Gravity and Culture in Foreign Portfolio Investment - LUCEY, BRIAN MICHAEL; KEARNEY, COLM (My University, 2011)
Using panel regression estimates from the IMF?s CPIS survey of foreign debt and equity portfolios across 174 originating and 50 destination countries from 2001 to 2007, we clarify the role of culture and extend the set of cultural variables that have been investigated in gravity models of foreign portfolio investment (FPI). Incorporating Hofstede?s cultural dimensions of individualism, masculinity, power distance and uncertainty avoidance, we show how cultural traits in both originating and destination countries, as well as the cultural distances that separate them, interact with geographic distance and other gravity variables to determine global FPI patterns. We find hitherto unreported effects and show that while gravity always deters FPI, aspects of culture and cultural distance can offset this by supporting FPI.
PUBLISHED
Keywords: Economics; Business; FPI; Home Bias